Teori Belajar Humanistik dan Implikasinya terhadap Pembelajaran Pendidikan Agama Islam - Budi Agus Sumantri; Nurul Ahmad (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2019)
This study aims to describe humanistic learning theory and its implications for the learning of Islamic Education. This research method uses library research or library research to be analyzed and concluded. Research data is obtained from recording books and journals. The results of this study contain an understanding of humanistic learning, humanistic learning figures listed: 1) Abraham Maslow as follows; a) Abraham Maslow's biography, b) Abraham Maslow's humanistic learning theory c) Implications of Abraham Maslow's Theory in Islamic Education. 2) Carl Rogers's humanistic learning theory and the implications of Carl Rogers's theory in learning Islamic Education. Conclusion of humanistic theories to humanize humans. the learning process is considered successful if the student discusses his environment and claims himself. Students in the learning process must try to make it more slowly and able to achieve self-actualization as well as possible.